Treatment of Acute Cholecystitis at Safety-Net Hospitals: Analysis of the National Inpatient Sample. Issue 1 (January 2020) - Singh, Supreet; Armenia, Sarah J.; Merchant, Aziz; Livingston, David H.; Glass, Nina E.
Evidence supports index cholecystectomy as the quality of care for patients admitted with acute cholecystitis. We sought to examine the role of hospital safety-net status on whether patients received appropriate index procedures for cholecystitis. The National Inpatient Sample was queried for patients with acute cholecystitis. Proportion of Medicaid and uninsured discharges were used to define safety-net hospitals (SNHs). Multivariate logistic regression was used to calculate associations between the frequency of index cholecystectomy and prolonged length of stay (LOS), and the effect of SNH designation. SNHs and non-SNHs had similar rates of index cholecystectomy in all geographic regions, except in the northeast, where the likelihood of having an index cholecystectomy was lower at SNHs. Patients at SNHs had longer LOS for acute cholecystitis, regardless of index or delayed cholecystectomy. When controlling for insurance status, patients at SNHs had longer LOS than those at non-SNHs. There was also increased LOS in SNHs in the Midwest, in urban hospitals, and in large hospitals. Our data showed no difference in the frequency of index cholecystectomy overall between SNHs and non-SNHs, except in the northeast. The variability and increased LOS at SNHs highlight potential opportunities to improve quality and decrease cost of care at our most vulnerable hospitals.